Socio-demographic aspects of "emerging adulthood" in the context of cultural changes in Poland compared to Europe = Społeczno-demograficzne aspekty "stającej się dorosłości" w kontekście zmian kulturowych w Polsce na tle Europy - Zielińska, Maria; Wróbel, Robert (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to identify and describe phenomena associated with the important phase of the individual`s life, i.e. transition to adulthood. The authors of the article attempt to determine the causes and consequences of changes taking place in this period of life. Based on the Eurostat database (http://ec.europa.eu/eurostat/data/database) that illustrates the phenomena of "nesting", entering the labour market, and starting a family (marriage, giving birth to the first child), significant transformations of the models of young people`s life are presented in the context of traditional markers of adulthood. The article refers to sociological concepts of youth, cultural and social changes. In particular, the concepts developed by Jeffrey Arnett, Ronald Inglehart and Ulrich Beek are useful for explaining the recorded trends.
Keywords: emerging adulthood; transition to adulthood; markers of adulthood; youth; social change; cultural channge; stająca się dorosłość; przechodzenie do dorosłości; markery dorosłości; młodzież; zmiana społeczna; zmiana kulturowa